2012
DOI: 10.1111/j.1600-0714.2012.01188.x
|View full text |Cite
|
Sign up to set email alerts
|

Nevoid basal cell carcinoma syndrome: a 40‐year study in the South African population

Abstract: The results of this study indicate that there was a low frequency of falx cerebri calcifications, BCCs, skull, and rib anomalies in this sample compared to other population groups. These differences could be attributed to genetic, racial, and environmental factors. Future studies are needed to compile diagnostic criteria specific to different population groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…The literature reports wide variation in the incidence of KCOTs in NBCCS patients ranging from 62%[ 47 ] to 100%. [ 48 49 50 ] This association has been found to be 100% in our case series. Usually, multiple keratocysts are found in NBCCS ranging from 1 to 30 in number, average being 5.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The literature reports wide variation in the incidence of KCOTs in NBCCS patients ranging from 62%[ 47 ] to 100%. [ 48 49 50 ] This association has been found to be 100% in our case series. Usually, multiple keratocysts are found in NBCCS ranging from 1 to 30 in number, average being 5.…”
Section: Discussionsupporting
confidence: 64%
“…[ 3 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 ] The frequency of findings in these patients in Indian literature combined with 5 patients in our case series was then compared with studies in different parts of the world and is presented in Table 5 . [ 43 44 45 46 47 48 49 50 51 ]…”
Section: Methodsmentioning
confidence: 99%
“…These data support the previous findings showing that these cysts are diagnosed at a younger age-according to Jung et al, 17 in the second decade of life-in patients with NBCCS. 18 OKCs can recur long after treatment has been performed. Oikarinen et al 19 reported recurrences 14 to 21 years after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Keratocystic odontogenic tumor also known as OKC includes about 11 % of all cysts of jaws [9] and occurs in more than 75 % of Gorlin's syndrome patients [6,10,11]. The prevalent age is second and third decades and it has a slight male tendency.…”
Section: Discussionmentioning
confidence: 99%